African Initiated Churches - Ranger, Terence (Transformation, 2007)
Idioms of African religion have enabled African men and women to respond to Christianity and to place their hopes in it. The idioms and new ideas of missions had a tremendous influence on the prophetic, spiritual African churches, helping to ensure that they would emerge as Christian churches rather than as re-statements of African religion. Some African churches did advocate the performance of ancestral rituals but stressed the need for dignity and sobriety in worship on the one hand and the acknowledgement of the cen-trality of preaching and the Bible on the other hand. Noisy ill-disciplined enthusiasm was strongly disapproved and yet the historic mission churches were not averse to experimenting with new ideas of inculturation.